CONVERSION IN STRAINS OF HISTOPLASMA CAPSULATUM - Pine, Leo (1962)
Pine, Leo (Duke University, Durham, N. C.) and Robert E. Webster. Conversion in strains of Histoplasma capsulatum. J. Bacteriol. 83:149–157. 1962—Photographs of mycelial elements taken at various time intervals from a single strain of Histoplasma capsulatum have shown the direct conversion of microconidia to yeast cells by polar and nonpolar budding, the formation of yeast cells by budding of hyphal cells, and the probable conversion of hyphal cells to yeast phase by monilial chain formation. In addition, studies of fixed-slide preparations of a second strain have indicated the formation of stalked yeast cells arising in a manner similar to that observed for microconidia formation but, apparently, by-passing the microconidial stage. These observations are discussed briefly in regard to temperature-induced changes in cell-wall synthesis during conversion.